2018
DOI: 10.1038/s41598-018-20784-5
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial asymmetries do not modulate the cheerleader effect

Abstract: The cheerleader effect occurs when the same individual appears to be more attractive when seen in a group, compared to alone. As observers over-attend to visual information presented in the left visual field, we investigated whether the spatial arrangement of the faces in a group would influence the magnitude of the cheerleader effect. In Experiment 1, target faces were presented twice in the centre of the display: once alone, and once in a group. Group images featured two distractor faces, which were presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(73 citation statements)
references
References 60 publications
(121 reference statements)
4
68
1
Order By: Relevance
“…A positive change value indicates that a face has become more attractive in a group, whereas a negative value represents a decrease in attractiveness. A one sample t-test is then used to determine whether the change in attractiveness differs from zero and is statistically significant 13,16 . Using this analytic approach, we have previously shown that the cheerleader effect occurs with a medium effect size (d = .60) 13 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A positive change value indicates that a face has become more attractive in a group, whereas a negative value represents a decrease in attractiveness. A one sample t-test is then used to determine whether the change in attractiveness differs from zero and is statistically significant 13,16 . Using this analytic approach, we have previously shown that the cheerleader effect occurs with a medium effect size (d = .60) 13 .…”
Section: Methodsmentioning
confidence: 99%
“…A one sample t-test is then used to determine whether the change in attractiveness differs from zero and is statistically significant 13,16 . Using this analytic approach, we have previously shown that the cheerleader effect occurs with a medium effect size (d = .60) 13 . An a priori power analysis indicated that a sample of 27 participants was required to achieve 85% power to detect an effect of d = 0.60 in a two-tailed, one sample ttest with an alpha of .05 52 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations